An application of SPI (Standardized Precipitation Index) to monthly rainfall data in Pernambuco between 1991-2019 (Research, Society and Development, 2023)
The determination and classification of regions prone to critical weather events, both intense rainfall and drought periods, are of utmost importance in the context of climate variability. In the Brazilian Northeast, a semi-arid region, drought is a recurring problem, while intense weather events such as heavy rains and landslides affect metropolitan areas and cause disasters. The state of Pernambuco shows a trend of extreme weather events, with long periods of drought and intense rainfall, which is responsible for numerous natural disasters in the state. The objective of this study was to analyze and classify, in an objective manner, the climate variability between 1991 and 2019 in the five stations of Pernambuco represented by Recife, Palmares, Itaíba, Salgueiro, and Petrolina, based on different time scales (1, 3, 6, 9, 12, 24, and 36 months). For this purpose, the Standardized Precipitation Index (SPI) was used, developed to classify dry and wet conditions according to severity. Through the analysis, it was observed that the smaller scales SPI-1 and SPI-3 revealed the onset and trajectory of each event, while the other scales identified the most intense and prolonged events. The results obtained indicated that drought periods had longer duration and intensity, with the driest month in Itaíba being -4.416 (SPI-3) in August 2018. However, rainy periods occurred more frequently in the stations, with the wettest month being in Palmares with 2.928 (SPI-3) in September 2000.